Biomechanical Characterization of Human Pluripotent Stem Cell-Derived Cardiomyocytes by Use of Atomic Force Microscopy - Pribyl, Jan; Pešl, Martin; Caluori, Guido; Acimovic, Ivana; Jelinkova, Sarka; Dvorak, Petr; Skladal, Petr; Rotrekl, Vladimir (Methods in molecular biology (Clifton, N.J.), 2019)
Atomic force microscopy (AFM) is not only a high-resolution imaging technique but also a sensitive tool able to study biomechanical properties of bio-samples (biomolecules, cells) in native conditions-i.e., in buffered solutions (culturing media) and stable temperature (mostly 37 °C). Micromechanical transducers (cantilevers) are often used to map surface stiffness distribution, adhesion forces, and viscoelastic parameters of living cells; however, they can also be used to monitor time course of cardiomyocytes contraction dynamics (e.g. beating rate, relaxation time), together with other biomechanical properties. Here we describe the construction of an AFM-based biosensor setup designed to study the biomechanical properties of cardiomyocyte clusters, through the use of standard uncoated silicon nitride cantilevers. Force-time curves (mechanocardiograms, MCG) are recorded continuously in real time and in the presence of cardiomyocyte-contraction affecting drugs (e.g., isoproterenol, metoprolol) in the medium, under physiological conditions. The average value of contraction force and the beat rate, as basic biomechanical parameters, represent pharmacological indicators of different phenotype features. Robustness, low computational requirements, and optimal spatial sensitivity (detection limit 200 pN, respectively 20 nm displacement) are the main advantages of the presented method.
Keywords: mikroskopie atomárních sil; Biomechanical characterization; Human stem cell; Pluripotent Stem Cells; Myocytes, Cardiac; lidé; Atomic force microscopy; Cardiomyocyte contraction; Drug testing; Drug Evaluation, Preclinical; Biosensing Techniques; biomechanika; preklinické hodnocení léčiv; pluripotentní kmenové buňky; biosenzitivní techniky; Microscopy, Atomic Force; Biomechanical Phenomena; kardiomyocyty; Humans